Comparative trial of cefonicid and cefamandole in the therapy of community-acquired pneumonia. - Wallace, R J (1982)
Cefonicid (Smith Kline & French Laboratories; D-75073) is a new parenteral cephalosporin with a markedly long half-life, high serum levels, and good in vitro activity against Haemophilus influenzae. Patients with community-acquired pneumonia were randomized 2:1 to receive cefonicid, 1 g daily (21 cases) or cefamandole, 1 g every 6 h (12 cases). The two groups were similar, except that the cefonicid patients were older (mean 42 versus 31 years). Peak serum levels of cefonicid averaged 133 microgram/ml after intravenous and 83 microgram/ml after intramuscular administration compared with 55 microgram/ml with intravenous cefamandole. All 9 patients on intramuscular cefonicid and 8 or 12 patients on intravenous cefonicid had trough serum levels of greater than 2.0 microgram/ml at 24 h. Sputum levels of cefonicid were usually between 2.0 and 4.0 microgram/ml and did not correlate with serum levels. Cefonicid was well tolerated, and all cefonicid patients responded clinically. Sputum cultures for H. influenzae or Streptococcus pneumoniae became negative in 6 of 7 cefamandole patients and 13 or 15 cefonicid patients. In in vitro studies, cefonicid inhibited 90% of beta-lactamase-negative h. influenzae at 0.5 microgram/ml and beta-lactamase-positive strains at 2.0 microgram/ml. Cefonicid inhibited 50% of S. pneumoniae at 1.6 microgram/ml, but required 6.4 microgram/ml to inhibit 90%. Cefonicid once a day appears to be as safe and as effective as cefamandole four times a day for therapy of community-acquired pneumonia.